Assessing the antioxidant antibacterial and toxic potential of quercus floribunda lindl bark - Bhattarai, Govinda; Sharma, Khaga Raj; Raj Jaishi, Dipak (BIBECHANA, 2025)
Since ancient times, herbal medical practitioners have been treating a wide range of conditions, from basic to life-threatening, with traditional or folk remedies. Phytochemicals are incredibly helpful in defending against numerous diseases in human beings. Due to their affordability and lack of side effects, herbal medicines have replaced synthetic drugs in many countries. The goal of the present study is to analyze the total phenolic content (TPC) and total tannin content (TTC) by the Folin-Ciocalteu method, total flavonoids content by the Aluminium chloride method, DPPH radical scavenging activity, cytotoxicity and antimicrobial activity by agar-well diffusion method. The dried bark of the Quercus floribunda Lindl was powdered, and then the extract was prepared in different solvents chosen based on their polarity using the cold maceration technique. Among different crude extracts, ethyl acetate extract has a high TPC (127.23 ± 1.65 mg GAE/g), and DCM has the lowest TPC (9.25 ± 0.69 mg GAE/g). Also, hexane extract shows high TFC (61.72 ± 4.01 mg QE/g), and ethanolic extract shows the least TFC content (3.97 ± 1.03 mg QE/g). Furthermore, ethanolic extract had the highest TTC which is 49.91 ± 1.0 mg TAE/g, and least TTC value in hexane extract which is 5.51 ± 1.3 mg TAE/g. Along with this, methanolic extract showed good antioxidant ability with IC50 of 12.70 ± 0.37 µg/ mL. In the case of the antimicrobial susceptibility test, the ethanolic and ethyl acetate extract of bark was found to be effective against Escherchia coli (ATCC 25912) with a zone of inhibition of 15 mm, equal to positive control, and neomycin. Ethyl acetate extract is also found effective against Shigella sonnei (ATCC 25931) with a zone of inhibition of 22 mm. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were also estimated in two different bacterial strains. For methanolic extract, the MIC value for Gram-positive Staphylococcus aureus (ATCC 43300) was 3.125 mg/mL, and Gram- negative Shigella sonnei was 3.125 mg/mL, and the MBC was 25 mg/mL for both strains. The methanolic extract shows good cytotoxicity against brine shrimp nauplii with LC50 of 40.55 µg/mL. Thus, from the overall study, the bark of Quercus floribunda Lindl could be used as a natural source to isolate antibiotics and antioxidants.